Connection between Built Environment and Travel Behavior: Propensity score approach under a continuous treatment Regime. Issue 1 (January 2014) - Parady, Giancarlos Troncoso; Takami, Kiyoshi; Harata, Noboru
In recent years, the compact city concept has become a paradigm of sustainable urban development under the premise that mixed-use, high-density cities can significantly reduce automobile dependency and promote the use of alternative modes. This claim, however, hinges on the existence of a true causal mechanism between the built environment and travel behavior. This study tackled the causality problem by using a propensity score approach but differed from previous studies in that this study relaxed the binary treatment assumption (i.e., urban versus suburban) and assumed a continuous treatment of urbanization level, estimated as a latent variable. Methodologically, the propensity score stratification method used was successful in mitigating residential self-selection bias on estimates of the effect of the built environment on nonwork trip frequency and traveled distance. Overestimation ranges for the direct regression estimates against the estimates stratified on the propensity score ranged from 6% to 36%. Findings suggested the existence of a causal mode substitution mechanism from car to nonmotorized modes given positive increases in the latent score of urbanization level.